INCORPORATING VISUAL NOVEL GAMES TO IMPROVE STUDENTS’ LEARNING INTEREST IN ENGLISH - Rivaldi, Muh.; Aeni, Nur; Asriati, Asriati (Universitas Negeri Makassar, 2024)
This research investigates the role of visual novel games in enhancing the learning interest and comprehension of 11th-grade nursing students at SMK Baznas Sulsel in English subjects. Adopting a qualitative approach, the study examines the effects of interactive, story-driven learning on student engagement and understanding. Data collected through student interviews indicate that the narrative structure and visual elements of visual novels make English lessons more appealing and accessible, fostering a supportive learning environment. Students reported that the interactive format of visual novels encouraged active participation and made complex language concepts easier to grasp, thus promoting both interest and deeper comprehension. These findings suggest that visual novels can be an effective educational tool for making English more engaging and relevant, especially in vocational settings. Based on the study’s positive outcomes, it is recommended that educators consider integrating visual novels into the English curriculum as a way to support motivation and understanding. Future research is suggested to assess the broader application of visual novels in other vocational subjects to evaluate if similar benefits can be achieved across different educational fields. This study contributes to the growing interest in innovative, game-based learning methods for enhancing student outcomes in language education.